The influence of work motivation and work discipline on employee performance at PT Samsung Electronics Indonesia, South Jakarta Branch - Siska Yunanti; Salma Sa'idatul Misykiyah (Indonesia Accounting Research Journal, 2025)
The purpose of this study was to determine whether work motivation and work discipline have a partial and simultaneous impact on employee performance at PT. Samsung Electronics Indonesia. A quantitative method was used. The sample consisted of 76 respondents, selected through a saturated sampling technique. Validity, reliability, classical assumptions, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing were used to analyze the data. With the regression equation, the results of the study indicate that work motivation and work discipline have a significant effect on employee performance. Y = 7.482 + 0.337X1 + 0.504X2. The correlation coefficient, or the level of influence between the independent variable and the dependent variable, is 0.850. The coefficient of determination, or the contribution of simultaneous influence, is 0.722, or 72.2%, and other factors influence 27.8% of the total. The F table value is greater than the calculated F, or (94.890 is greater than 3.120). Therefore, H0 is rejected and H3 is accepted, indicating that work motivation and work discipline affect the performance of PT Samsun employees.